Home public services in Ecuador. Collection and analysis of related documents. - Cedeño Alcívar, Jenny; Jara Iñiguez, Irma (SATHIRI, 2019)
The Ecuadorian State dedicates in the Constitution the guarantee, without any discrimination, to the effective enjoyment of the rights of the users of domiciliary public services within the framework of international instruments. A digital search of studies on home public services in Quito and its scope was carried out. The institutions that provide drinking water, sanitation, electricity, liquefied petroleum gas and fixed telephony services are obliged to provide fair prices and tariffs, to establish control and regulation thereof, and to guarantee that these services and their provision respond to the principles of obligatory nature, generality, uniformity, efficiency, responsibility, universality, accessibility, regularity, continuity, quality and solidarity. It is a qualitative analytical-descriptive research. It was reviewed in the official pages of public institutions, public and private companies, academic and institutional digital repositories and specialized search engines, the different studies on the provision of home public services were published. The selected reports were systematically reviewed and the types of studies, the scope and the institutions that prepared them were established. The main legacies noted in the Constitution of the Republic of Ecuador were analyzed in accordance with the international instruments on access to home public services, the Millennium Development Goals and Sustainable Development of the United Nations, the National Plan for Good Living 2017, and the national regulations in force in 2017 that indicate the provision of services.